The effect of time administration and concentration of probiotics of the growth and yield of suri cucumber plants (Cucumis melo L. var reticulatus Naudin). - Iswita Iswita; Susylowati Susylowati; Eliyani Eliyani (Universitas 17 Agustus 1945 Samarinda, 2019)
Suri cucumber (Cucumis melo L. var reticulatus Naudin) is an annual plant. Probiotics is not a fertilizer in general, but materials containing effective microorganism that can help decompose the material present in the soil and can be used to inhibit the growth of plant pests and diseases in the soil, this study aims to determine: (1) the interaction between time and concentration on growth and yield on suri cucumber plants; (2) Time of giving probiotics that are appropriate for growth and yield on suri cucumber plants; and (3) Probiotic concentrations that are appropriate for growth and yield on suri cucumber plants. This research was conducted from April to July 2018 at the Kelurahan Loa Tebu, Kecamatan Tenggarong, Kabupaten Kutai Kartanegara. Factorial designs are arranged in Complete Randomized Design (CRD) with 6 replications. The first factor is the time administration of (W) probiotics at 7 am 12(w1)